Molecular insights into enhanced resistance of Papaver somniferum against downy mildew by application of endophyte bacteria Microbacterium sp. SMR1. Issue 4 (5th September 2021) - Ray, Tania; Pandey, Alok; Pandey, Shiv S.; Singh, Sucheta; Shanker, Karuna; Kalra, Alok
Abstract: Downy mildew is one of the most serious diseases of Papaver somniferum . Endophytes isolated from different parts of P. somniferum were screened for their ability to enhance resistance against downy mildew caused by the obligate biotrophic oomycete Peronospora meconopsidis . Two endophytes (SMR1 and SMR2) reduced the downy mildew on three P. somniferum genotypes (Sampada, J‐16, and I‐14). SMR1 ( Microbacterium sp .) also enhanced the resistance of P. somniferum against downy mildew under field conditions. The biochemical markers of plant susceptibility under biotic stresses (proline and malondialdehyde) were found to be reduced in P. somniferum upon SMR1 treatment. To understand the mechanisms underlying the enhanced resistance to downy mildew in SMR1 endophyte‐treated P. somniferum genotype J‐16, we compared the expression profiles using the next‐generation RNA sequencing approach between P. somniferum pretreated with SMR1 and untreated endophyte‐free control plants following exposure to downy mildew pathogen. Comparative transcriptome analysis revealed differential expression of transcripts belonging to broad classes of signal transduction, protein modification, disease/defense proteins, transcription factors, and phytohormones in SMR1‐primed P. somniferum after infection with downy mildew pathogen. Furthermore, enhanced salicylic acid content was observed in SMR1‐primed P. somniferum after exposure to downy mildew pathogen. This study sheds light on molecular mechanisms underlying enhanced resistance to downy mildew in SMR1‐primed P. somniferum . Finally, we propose that the SA‐dependent defense pathway, the hallmark of systemic acquired resistance, is activated in SMR1‐primed P. somniferum, triggering the endophyte‐induced resistance.